English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Then using the same method solve:3x+4y=-6 and under that 5x+6y=-21/2

2007-01-11 03:35:43 · 6 answers · asked by pkbrauer 1 in Science & Mathematics Mathematics

6 answers

3x-y=-1 ---(1)
4x+2y=22 ---(2)

(1)*2 + (2)
6x+4x = -2+22
10x=20
x=2
by (1) y=3*2+1=7

Similar way you can solve the other two equations.
just try.

2007-01-11 03:43:31 · answer #1 · answered by hirunisha 2 · 0 0

divide thesecond eq by 2, add to the first equation and the result is 5x = 10 or x = 2 plug x back into the first eq and solve for y and get y = 3*2 + 1 = 7

2007-01-11 03:59:33 · answer #2 · answered by 1ofSelby's 6 · 0 0

3x-y=-1 ------1
4x+2y=22------2

multiply first equation by 2
becomes

6x-2y=-2
4x+2y=22

-2x and 2x cancels out

6x+4x=10x
-2+22=20

10x=20x
x=2

putting x=2 in equation 1

3(2)-y=-1
6-y=-1
6+1=y
7=y

thus x=2 and y=7

2007-01-11 03:53:50 · answer #3 · answered by gaurav 1 · 0 0

(1) 3x-y=-1
(2) 4x+2y=22

Multiply (1) by 2 then add (1) and (2):
6x-2y=-2
4x+2y=22
_____________
10x+0=20
x=20/10=2

Now substitute x in (1)
3*2-y=-1
6+1=y
y=7

2007-01-11 03:46:54 · answer #4 · answered by ENA 2 · 0 0

x=2, y =7

x = 3, y = -15/4

2007-01-11 04:04:43 · answer #5 · answered by ag_iitkgp 7 · 0 0

3x-y=-1...1
4x+2y=22...2
double eqn.1
6x-2y=-2....3
from 2&3 adding we have
10x=20
x=2
y=7

2007-01-11 03:55:34 · answer #6 · answered by openpsychy 6 · 0 0

fedest.com, questions and answers